Pengaruh Kompensasi, Motivasi, dan Kepuasan Kerja terhadap Produktivitas Kerja Karyawan PT. Perkebunan Nusantara IX Semarang (Studi Pada Karyawan Bagian Produksi PT. Perkebunan Nusantara IX Kebun Ngobo Ungaran) - Rangga Aditya Widodo; Haryani Haryani (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2021)
The desired objective of this research activity is to examine and analyze the effect of compensation, motivation and job satisfaction on the work productivity of employees at PT. Nusantara Plantation IX Ngobo Ungaran Plantation. The population in this study were all production employees at PT. Nusantara Plantation IX Ngobo Ungaran Plantation, totaling 50 people. In this study, samples/respondents were taken from the entire population of 50 respondents, using saturated sampling techniques. Based on the discussion, the following conclusions can be drawn: Testing the compensation hypothesis on employee work productivity shows that the value of t count = 2.805 > t table = 1.684 with a significance number = 0.007 <α = 0.05 (significant). Thus, the hypothesis (H1) that compensation has a positive effect on employee work productivity is proven. Testing the hypothesis of motivation on employee productivity shows that the value of t count = 3.972 > t table = 1.684 with a significance number = 0.000 < α = 0.05 (significant). Thus, the hypothesis (H2) that motivation has a positive effect on employee work productivity is proven.